Use of CMC Na as Gelling Agent in Nanoemulgel Formulation of Methanol Extract of Sappan Wood (Caesalpinia sappan L) - Dwi Saryanti; Iwan Setiawan; Hendri Hari Dayanto (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Sappan wood ( Caesalpinia sappan L.) contains brazilin including isoflavonoids which act as antimicrobials (against bacteria on skin) and antioxidants. Nano technology increases surface area, enhance stability, reduces skin irritation, protects from degradation, and has good drug delivery. Nano emulsion preparations can help permeability of the drug on the membrane surface. Nanoemulgel preparations can provide stability and good drug release compared to mixing drugs directly in a gel base. The purpose of this study were to determine the effect of different concentrations of CMC-Na gelling agents and which concentration of CMC-Na gelling agents that can produce the best nanoemulgel preparations. Nanoemulsion made from isopropyl myristate as oil phase, tween 80 as surfactant and polyethylenglycol as co-surfactant. Nanoemulsion formulations were tested by measurement of % transmittance by UV-Vis spectrophotometry at a wavelength 650nm. Nanoemulgel is made from nano emulsions used basis of CMC-Na at concentrations 3%, 4%, and 5%. The results showed percent transmittance was 71.86%. The results of physical quality and stability tests of the nanomulgel wood preparations showed an influence on the physical properties such as adhesion, dispersion and viscosity, the greater concentration of CMC-Na gelling agents in nanoemulgel preparations, the greater values adhesion and viscosity, while the spreadability was smaller. Concentration of CMC-Na gelling agent that produced the best of sappan wood nanoemulgel ( Caesalpinia sappan L.) was 5% that stable by freeze-thaw testing.